Fundamental molecular biology - Allison, Lizabeth A. (John Wiley & Sons, 2012)
New to this edition: Discovery figures. Each discovery figure takes a macro-to-micro approach, showing students how to look at the big picture and the details of important topics. Real Data is presented thorugh the text to give students the opportunity to work with real experimental details. Real Data icons appear in the margins to notify the students when real data appears. Balanced presentation of both eukaryotic and prokaryotic examples helps students understand the variation of cellular processes across organisms. The Wiley Resource Kit provides additional assests for both instructors and students and can be delivered through any Learning Management System (LMS). -- from back cover.